2013
DOI: 10.14419/ijamr.v2i2.939
|View full text |Cite
|
Sign up to set email alerts
|

Numerical Solution of Unsteady Hydromagnetic Natural Convection Flow of Heat Absorbing Fluid past an Impulsively Moving Vertical Plate with Ramped Temperature

Abstract: A numerical investigation of unsteady hydromagnetic natural convection flow of a viscous, incompressible, electrically conducting and heat absorbing fluid past an impulsively moving vertical plate with ramped temperature embedded in a porous medium in the presence of thermal diffusion is carried out. The governing equations are solved numerically by Crank-Nicolson implicit finite difference scheme. The numerical solution for fluid velocity and fluid temperature are depicted graphically whereas the numerical va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
18
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 42 publications
2
18
0
Order By: Relevance
“…Mbeledogu and Ogulu (2007) obtained analytical closed form solution of unsteady hydromagnetic natural convection flow of a rotating, incompressible, viscous Boussinesq fluid in the presence of radiative heat transfer and first order chemical reaction. The influence of radiation and rotation on unsteady hydromagnetic free convection flow past an impulsively moving infinite vertical plate with ramped temperature in a porous medium is investigated by Seth et al (2013). Jonah Philliph et al (2014) considered the problem of rotating magnetohydrodynamic heat and mass transfer free convection flow past an exponentially accelerated isothermal vertical plate in the presence of variable mass diffusion.…”
Section: Frontiers In Heat and Mass Transfermentioning
confidence: 99%
See 1 more Smart Citation
“…Mbeledogu and Ogulu (2007) obtained analytical closed form solution of unsteady hydromagnetic natural convection flow of a rotating, incompressible, viscous Boussinesq fluid in the presence of radiative heat transfer and first order chemical reaction. The influence of radiation and rotation on unsteady hydromagnetic free convection flow past an impulsively moving infinite vertical plate with ramped temperature in a porous medium is investigated by Seth et al (2013). Jonah Philliph et al (2014) considered the problem of rotating magnetohydrodynamic heat and mass transfer free convection flow past an exponentially accelerated isothermal vertical plate in the presence of variable mass diffusion.…”
Section: Frontiers In Heat and Mass Transfermentioning
confidence: 99%
“…Although these system parameters play significant role in determining the flow features of the hydromagnetic natural convection flows. Seth et al (2014) extended the works of Seth et al (2013) and Jonah Philliph et al (2014) and investigated the influence of Hall current, permeability of the medium, heat absorption/radiation and chemical reaction on hydromagnetic natural convection flow past an impulsively moving isothermal vertical plate with uniform species concentration. Seth et al (2015) considered the influence of Hall current, permeability and heat absorption on hydromagnetic natural convection flow past an exponentially accelerated vertical plate with ramped plate temperature but they have not considered the effect of rotation and species concentration in their problem.…”
Section: Frontiers In Heat and Mass Transfermentioning
confidence: 99%
“…Seth and Ansari (2010) analyzed MHD natural convection flow past an impulsively Moving vertical plate with ramped wall temperature in the presence of thermal diffusion with heat absorption. Seth et al (2013) studied effects of thermal radiation and rotation on unsteady hydromagnetic free convection flow past an impulsively moving vertical plate with ramped temperature in a porous medium. Seth et al (2014a) analyzed hydromagnetic natural convection flow with radiative heat transfer past an accelerated moving vertical plate with ramped temperature through a porous medium.…”
Section: Frontiers In Heat and Mass Transfermentioning
confidence: 99%
“…Jasmine Benazir et al 25 study focused on the effects of double dispersion, non-uniform heat source/sink and higher order chemical reaction on unsteady free convective, MHD Casson fluid flow over a vertical cone and flat plate saturated with porous medium. Seth et al 26 investigated on unsteady MHD natural convection flow with heat and mass transfer of an electrically conducting viscous incompressible chemically reactive and optically thin heat radiating fluid through a saturated porous medium past an infinite moving vertical plate with arbitrary ramped temperature. It is found that, for isothermal plate, the fluid temperature and, the rate of heat transfer at isothermal plate approaches steady state when 1.5 t  .…”
Section: I) Introductionmentioning
confidence: 99%